RANCANG BANGUN SISTEM TONGKAT SEBAGAI ALAT BANTU TUNANETRA MENGGUNAKAN SENSOR ULTRASONIK DAN PERINGATAN SUARA BERBASIS ARDUINO UNO - Hakim, Marwan; Rusdan, Rusdan (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Blindness is a condition in the eyes that does not function properly. Blind people use sticks as a guide to find out the conditions around them. The use of blind sticks can generally only detect objects in front of them, namely by touching the stick in front of them, so that blind people know that there is an object in front of them that must be avoided. However, this method can endanger blind people because blind people can hit obstacles in front of them, because the distance to find out the existence of obstacles is too close. This study discusses how a stick is a tool for blind people using ultrasonic sensors and Arduino Uno-based sound warnings that can help blind people walk. The results of this study are to produce a stick as a tool for blind people using ultrasonic sensors and Arduino Uno-based sound warnings. The tool will issue a sound warning if the ultrasonic sensor detects an obstacle, the maximum distance that will be detected depends on how much is set in the Arduino Uno program.